Targeting Cis-Regulatory Elements for Rice Grain Quality Improvement - Ding, Yu; Zhu, Jiannan; Zhao, Dongsheng; Liu, Qiaoquan; Yang, Qingqing; Zhang, Tao (Frontiers in Plant Science, 2021)
Rice is the most important source of food worldwide, providing energy and nutrition for more than half of the world’s population. Rice grain quality is a complex trait that is affected by several factors, such as the genotype and environment, and is a major target for rice breeders. Cis-regulatory elements (CREs) are regions of non-coding DNA that play a critical role in gene expression regulation. Compared with gene knockout, CRE modifications are able to fine tune the expression levels of target genes. Genome editing has provided opportunities to modify the genomes of organisms in a precise and predictable way. Recently, promoter modifications of coding genes using genome editing technologies in plant improvement have become popular. Here, we review recent results on the identification, characterization, and application of CREs involved in rice grain quality. We propose CREs as preferred potential targets to create allelic diversity and improve quality traits via genome editing strategies in rice. We also discuss potential challenges and experimental considerations for grain quality improvement in crop plants.